Excavations at the Langobard Cemetery in Kranj in 1905 - Nataša Nemeček (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The library of the National Museum of Slovenia contains both editions of Friedrich Rathgen's handbook Die Konservierung von Altertumsfunden (the first edition from 1898 and the second from 1915). It is of particular interest that the conservation methods described in the first Rathgen handbook could be directly connected to excavations of the Langobard Cemetery in Kranj in 1905. The excavations were followed closely by several newspapers at that time. For the conservation of finds, especially iron, the new methods developed by Theodor Blell-Tüngen and the Norwegian engineer Axel Krefting were used.